Unusual adult-onset cardiac rhabdomyomas in tuberous sclerosis complex: a case report - Nati-Castillo, H. A.; Quintero, Juan Manuel; Molina, Oswaldo Aguilar; Arias-Intriago, Marlon; Melgar Muñoz, Fernando P.; Izquierdo-Condoy, Juan S. (Frontiers in Medicine, 2024)
Tuberous sclerosis complex is a genetic neurocutaneous autosomal dominant syndrome, characterized by the development of multiple benign tumors (hamartomas) affecting various systems. Heart-benign tumors that result from the complex are called cardiac rhabdomyomas. Unlikely hamartomas that occur in other organs, cardiac rhabdomyomas are most prevalent in infants and very young children with tuberous sclerosis complex. We present a case of a young adult with tuberous sclerosis who had an unusual late diagnosis of cardiac rhabdomyomas.A 22-year-old male, afro-descendant patient, diagnosed with tuberous sclerosis complex in childhood, with refractory epilepsy managed with lacosamide. The patient came to medical consultation due to recent history of episodic, persistent chest pain in the sternal region, associated with physical effort. Echocardiography revealed a non-dilated left ventricle, with several rounded masses of high echogenicity without pedicles at the apical level, the largest measuring 14 x 11 mm, consistent with cardiac rhabdomyomas.Cardiac rhabdomyomas rarely develop in adulthood for individuals with tuberous sclerosis. These lateonset cases can exhibit various symptoms, from simple to complex presentations. Regular clinical check-ups are essential for adults with tuberous sclerosis complex.